2015
DOI: 10.1021/acs.nanolett.5b03938
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Nanotubes Based on Cyclodextrins for Ion-Channel Applications

Abstract: Biomimetic membrane channels offer a great potential for fundamental studies and applications. Here, we report the fabrication and characterization of short cyclodextrin nanotubes, their insertion into membranes, and cytotoxicity assay. Mass spectrometry and high-resolution transmission electron microscopy were used to confirm the synthesis pathway leading to the formation of short nanotubes and to describe their structural parameters in terms of length, diameter, and number of cyclodextrins. Our results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 36 publications
0
32
0
1
Order By: Relevance
“…β-CD and PPO with a molecular mass of 2000 g mol −1 (β-CDNT2000), γ-CD and PIB with a molecular mass of 2300 and 20 000 g mol −1 (γ-CDNT2300 and γ-CDNT20000, respectively) and γ-CD with two chains of PEO for a molecular mass of 1000 g mol −1 (γ-CDNT1000″). The synthesis of α-CDNTs has been previously described; 79 the preparation scheme is recalled in ESI Scheme S1. † MALDI-TOF MS analysis is performed both in linear and reflector modes to probe the various mass distributions and to attribute each peak in relation to the diversity of the structural content.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…β-CD and PPO with a molecular mass of 2000 g mol −1 (β-CDNT2000), γ-CD and PIB with a molecular mass of 2300 and 20 000 g mol −1 (γ-CDNT2300 and γ-CDNT20000, respectively) and γ-CD with two chains of PEO for a molecular mass of 1000 g mol −1 (γ-CDNT1000″). The synthesis of α-CDNTs has been previously described; 79 the preparation scheme is recalled in ESI Scheme S1. † MALDI-TOF MS analysis is performed both in linear and reflector modes to probe the various mass distributions and to attribute each peak in relation to the diversity of the structural content.…”
Section: Resultsmentioning
confidence: 99%
“…89,90 Recently, we successfully manufactured and characterized short biomimetic NTs based on α-CD with a sub-nanometric diameter. 79 We showed that these NTs form spontaneous transient ion channels in lipid membranes, the conductance of which was mainly due to the transport of ions. Interestingly, under our previous experimental conditions, these NTs did not alter the mitochondrial dehydrogenase activity or the morphology of living cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Within this context, much attention has been devoted to smart polymer-based 22 nanochannels, which bear the obvious advantages of high controllability, satisfactory reversibility, and remarkable conformational transition in response to external stimuli 23,24 . By producing diverse external stimuli, such as temperature, pH, light, or redox potential [25][26][27] , reversible tuning of ion transport across smart polymer-modified nanochannels can be achieved, which has resulted in wide applications for both material sciences and life sciences [28][29][30][31][32] .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, nanopores have similar nanometric length and diameter. They consist of either synthesized [17][18][19][20] or proteic 21,22 channels inserted in a lipid bilayer, or of a solid-state nanopore pierced in an ultra-thin dielectric membrane. 8,12,[23][24][25][26][27][28][29][30] The main advantage of protein channels is the reproducibility of their structure and their sensitiv-ity.…”
mentioning
confidence: 99%